10.2k views
1 vote
Question 13 I don’t know how to do it

Question 13 I don’t know how to do it-example-1
User Mjjohnson
by
5.8k points

1 Answer

6 votes

Answer:

y = -
(1)/(4) (x - 1)²(x + 2)(x + 6)

Explanation:

The roots from the graph are

x = - 6 , then factor is (x + 6)

x = - 2 , then factor is (x + 2)

x = 1 ( multiplicity 2 ) , then factor is (x - 1)² then

y = a(x - 1)²(x + 2)(x + 6) ← a is a multiplier

To find a substitute any point on the graph into the equation

Using (0, - 3 ), then

- 3 = a(- 1)²(2)(6) = 12a ( divide both sides by 12 )

-
(1)/(4) = a

Then

y = -
(1)/(4) (x - 1)²(x + 2)(x + 6)

User Villi
by
6.3k points